Liturgi Sabda Sebagai Komunikasi Antara Tuhan Dan Umat Di Paroki Santo Andreas Lasiana - Bonefantura Jemy Bria; Rusae, Yohanes (SOKO GURU: Jurnal Ilmu Pendidikan, 2026)
Abstract. The Liturgy of the Word is an integral part of the Eucharistic celebration which functions not only as a ritual but also as a divine communication event between God and His people. The Second Vatican Council in Sacrosanctum Concilium emphasizes that Christ is truly present in His Word when the Scriptures are proclaimed in the Church. This study aims to analyze the understanding, implementation, and experience of the faithful regarding the Liturgy of the Word as a form of communication with God at St. Andreas Lasiana Parish. A qualitative descriptive method with a phenomenological paradigm was employed. Data were collected through participatory observation, in-depth interviews, and documentation studies involving the parish priest, the liturgy team, lectors, and parishioners. The findings reveal that while the faithful have a theological understanding of the Liturgy of the Word, its implementation still faces challenges such as the quality of proclamation, the contextual relevance of homilies, and the low level of active participation. Internal factors (faith and spirituality) and external factors (liturgical setting and pastoral guidance) significantly influence the effectiveness of this communication. The study recommends ongoing liturgical formation and catechesis to enhance the faithful's appreciation of the Liturgy of the Word as a transformative encounter with God.